Pengaruh perendaman air hangat terhadap penurunan glukosa darah pada atlet bola voli putri PBVSI Kabupaten Pinrang - Ricardo Valentino L.; Syahrul Saleh (Seminar Nasional LP2M UNM, 2019)
This study aims to determine the effect of warm water immersion on the decrease of the blood glucose of volleyball athletes. This research is a One Group Pre-Test Design research. With a total sample of 20 people, based on the results of the data analysis obtained by the difference in glucose levels of normal water immersion groups Volleyball athletes obtained an average value of -4. 30 and obtained a P value of 0.035 (P <0.05). From the data of glucose level difference in warm water immersion group, female volleyball athletes PBVSI Pinrang Regency obtained an average value of 16.2 and obtained a P value of 0.035 (P <0.05). So it can be concluded that there is a difference in the effect of ordinary water immersion and warm water immersion on glucose levels in PBVSI female volleyball athletes in Pinrang Regency with a difference of 20.5 mg / dl where the soaking warm water is more influential in reducing blood glucose levels.